The Use of the Braden Scale in Assessing Pressure Ulcers in Turkey A Systematic Review - (:unkn) unknown (LIPPINCOTT WILLIAMS & WILKINS, 2015)
OBJECTIVE: The goal of this systematic review was to reach scientific generalizations regarding the assessment of risk for pressure ulcers based on the results of previous studies that made use of the Braden Scale. DATA SOURCES: This research was performed by using a retrospective screening of studies relevant to the subject. In Turkey, the first validity and reliability study for the Braden Scale was performed by Oguz and Olgun in 1998. For this reason, the authors' research was conducted between March 2, 2012, and August 4, 2012, as a systematic review analysis by evaluating studies in Turkey that made use of the Braden Scale between 1998 and 2012. Screening was performed by using different combinations of 8 keywords in Turkish and English to scan a total of 10 national and international databases. A total of 2375 studies were evaluated, and 16 studies were included and considered within the context of this research. RESULTS AND CONCLUSIONS: It was determined that the studies considered within the context of the current research were conducted between 1998 and 2012; 5 of these studies were experimental and 11 were descriptive; the sample size varied between 22 and 422; the majority were performed in intensive care units; and the study samples were mostly composed of patients. The Braden Scale was used in these studies for forming samples by identifying high-risk patients. Two studies evaluated the reliability of the Braden Scale, whereas 7 other studies calculated the reliability coefficient. Only 1 study included results for sensitivity, specificity, positive predictive value, and negative predictive value (which represent the predictive criteria of assessment tools). Four studies indicated cutoff values, which varied between 14 and 18. A general evaluation of these studies' results revealed limited evidence of effective risk assessment by the Braden Scale.
Keywords: INTENSIVE-CARE UNITS; PREDICTIVE-VALIDITY; SORE RISK; PREVENTION; PREVALENCE; SAMPLE